2017
DOI: 10.1590/1414-431x20165796
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Treg cells and HBV genotype on sustained response and drug resistance in the treatment with nucleoside drugs

Abstract: We aimed to investigate the influence of regulatory T cells including CD4+CD25+, CD8+CD28- and hepatitis B virus (HBV) genotype on sustained virological response and tolerance of nucleoside drugs. One hundred and thirty-seven patients were enrolled. Lamivudine was administered to 84 patients. Entecavir was administered to the other 53 patients. Before treatment, biochemical tests, HBV DNA load, HBV serum level, HBV genotype, PB CD3+, CD4+, CD8+, CD4+CD25+/CD3+, and CD8+CD28-/CD3+ frequencies were measured. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, in contrast to this opinion, Zhang et al argue that Tregs (CD4 + CD25 + ) levels were lower in the group that responded to lamivudine treatment than in the group that did not respond. No significant change of Tregs was observed in the entecavir treatment group [112], which may be due to the difference in the specific markers selected for Tregs. Th17 cells mediate non-specific inflammation, and the Th17/Treg imbalance is associated with disease progression in patients with CHB infection [113].…”
Section: Tregs Response To Antiviral Therapymentioning
confidence: 79%
“…However, in contrast to this opinion, Zhang et al argue that Tregs (CD4 + CD25 + ) levels were lower in the group that responded to lamivudine treatment than in the group that did not respond. No significant change of Tregs was observed in the entecavir treatment group [112], which may be due to the difference in the specific markers selected for Tregs. Th17 cells mediate non-specific inflammation, and the Th17/Treg imbalance is associated with disease progression in patients with CHB infection [113].…”
Section: Tregs Response To Antiviral Therapymentioning
confidence: 79%
“…Nevertheless, Zhang et al contended that the levels of Tregs identified as CD4 + CD25 + were reduced in the cohort displaying a positive response to lamivudine treatment compared to the non‐responsive group. No significant change in Tregs was observed in the entecavir treatment group [98], possibly due to the difference in the specific markers selected for Tregs. Th17 cells mediate nonspecific inflammation, and the Th17/Treg imbalance is associated with disease progression in patients with CHB infection [99].…”
Section: Tregs In Chronic Hepatitis B Virus Infectionmentioning
confidence: 99%